Aberrations in the Body and in the Body Politic: The Eighteenth-Century Life of Benjamin Lay, Disabled Abolitionist - Kogan, Nathaniel Smith (Disability Studies Quarterly, 2016)
This article re-evaluates traditional interpretations and presentations of the (in)-famous eighteenth century Quaker abolitionist, Benjamin Lay, by arguing that his physical disability provided the foundation for his advocacy to eliminate slaveholding amongst his fellow Friends. The article will first establish the historical context Benjamin Lay's life and transatlantic travels to explain the roots of his abolitionist advocacy. Then, this article will analyze Lay's radical abolitionism both within the context of eighteenth-century Quaker antislavery and through the lens of disability history. This methodological approach will reveal that Lay displayed a clear awareness of his non-conforming body and the ways that its marginalizing effects empowered him to radically challenge the Quaker slaveholding establishment. The article will then analyze Lay's All Slave-Keepers, Apostates and argue that Lay rhetorically constructed his own disability in this text through both a religious lens and through the emerging Enlightenment concept of human aberrance and hierarchy. Finally, the article will conclude by analyzing some of the earliest visual representations of Lay's strange body and contend that the context in which they were commissioned and circulated forged a positive connection between Lay's disability and his abolitionist accomplishments.